TAX PLANNING ANALYSIS THROUGH THE DEPRECIATION AND REVALUATION METHODS OF FIXED ASSETS TO MINIMUM TAX LOAD AT PT. TASPEN (PERSERO) TASIKMALAYA BRANCH - Faisal, Deni (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of this thesis research is to determine tax planning through the depreciation method and fixed asset revaluation of the tax burden at PT. Taspen (Persero) Tasikmalaya Main Branch. This research method uses descriptive research. This study collects facts and identifies data that discusses tax planning issues in the field of depreciation and revaluation of fixed assets against the tax burden borne by the company. The results of this study are expected to provide input to the management of PT. Taspen (Persero) Tasikmalaya Main Branch in carrying out depreciation of fixed assets, it is better to pay attention to the latest tax laws in order to further optimize the allowable tax burden according to taxation and revaluation of fixed assets by PT. TASPEN (Persero) is not a requirement then PT..The conclusion of this research is that with the depreciation and revaluation of the company's fixed assets, PT. Taspen (Persero) Tasikmalaya Main Branch can save or minimize the tax burden that must be paid by the company